Mediating the uprising : narratives of gender and marriage in Syrian television drama - Joubin, Rebecca (Politics of marriage and gender: global issues in local contexts., 2020)
"Mediating the Uprising: Narratives of Gender and Marriage in Syrian Television Drama shows how gender and marriage metaphors inform post-uprising Syrian drama for various forms of cultural and political critique. These narratives have become complicated since the uprising due to the Syrian regime's effort to control the revolutionary discourse. As Syria's uprising spawned more terrorist groups, some drama creators became nostalgic for pre-war days. While for some screenwriters a return to pre-2011 life would be welcome after so much bloodshed, others advocated profound cultural and social transformation, instead. They employed marriage and gender metaphors in the stories they wrote to engage in political critique, even at the risk of creating marketing difficulties for the shows or they created escapist stories such as transnational adaptations and Old Damascus tales. Serving as heritage preservation, Mediating the Uprising underscores that television drama creators in Syria have many ways of engaging in protest, with gender and marriage at the heart of the polemic"--